Ambedkar’s interpretation of Buddhism (Bodhi Path, 2019)
Buddhism, the fourth largest world religion has become a subject of study in recent era. This paper shall examine the role of Dr Bhimrao Ramji Ambedkar in the renaissance of Buddhism in India and how Buddhism initiated by the Sakyamuni Buddha have served as a means for the emancipation of the deprived caste from oppression at the hands of the upper caste Hindus. Buddhism being a rational religion have thrown open the doors for all sentient being irrespective of one’s caste, creed, gender and so on. The Buddha stated -“One does not become a Brahmin by birth. One does not become an outcast by birth. One becomes a Brahmin by act. One becomes an outcast by act.”(Suttanipata, pp. 641) Ambedkar after his research in Buddhism became a devotee of the Buddha as he was impressed by His teachings based on the right to live and equality among human beings and was in opposition of an unjust, caste-based superstitious Indian society. The Buddha’s teaching termed as ‘Dhamma’ is not merely a composition of rituals, prayers, rules and regulation but a way of life. He paved the middle path for the sentient beings which is known as the Noble Eightfold Path. It is called the middle path because one avoids the two extremes that is one neither follows the path of self-mortification nor that of self-indulgence
Keywords: Ambedkar